Gynaecomastia in a male neutered cat with an adrenal tumour and associated hyperprogesteronism, hypercortisolism and hyperaldosteronism. Issue 2 (September 2021) - Yu, Jane; Lenord, Jason; Lau, Michelle; Brunel, Laurencie; Gray, Rachael; Donahoe, Shannon L; Boland, Lara
Case summary: A 7-year-old male neutered domestic longhair cat was presented with chronic progressive gynaecomastia, polydipsia, polyphagia, weight loss and poor fur regrowth. Sexualised behavioural changes were not reported and virilisation was not present on physical examination. Pertinent haematology, biochemistry and urinalysis findings at the time of referral included mild hypokalaemia. Left adrenomegaly and mild prostatomegaly were identified on a CT scan. Evaluation of adrenal hormones with a low-dose dexamethasone suppression test, serum progesterone, testosterone, oestradiol, plasma aldosterone, renin, plasma metanephrine and normetanephrine measurement supported a diagnosis of hyperprogesteronism, hyperaldosteronism and hypercortisolism. Adrenalectomy was performed and histopathology was consistent with an adrenocortical tumour. Clinical signs and hormone elevations resolved postoperatively. Relevance and novel information: To our knowledge, this is the second report of gynaecomastia secondary to an adrenal tumour in a male neutered cat and the first associated with hyperprogesteronism.